KONTRIBUSI MAHASISWA P3K UPI PURWAKARTA DALAM MEWUJUDKAN GENERASI LITERAT MELALUI WORKSHOP LITERASI DENGAN OUTPUT BUKU BACAAN DAN BUKU ENSIKLOPEDIA - Viola Handayani; Istiba Hikmatul Anwar; Yosha Sheptia; Tamara Noviani Fujia Suchi; Fitri Rohmatul Aulia; Nada Savaira Raihana; Jidan Fauzi; Teten Ginanjar Rahayu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Literacy culture develops not only as a mere hobby or passion for reading, but also as an effort that can be made to prepare us to face future challenges. The P3K UPI Purwakarta group at SDN 6 Nagrikaler held a community service activity in the form of a literacy workshop. This workshop aimed to increase students' interest in reading through reading books and encyclopedias. In this activity, teachers also participated in creating reading books and encyclopedias guided by students using the Canva application. The methods used in this study were lectures, discussions, and simulations/demonstrations of using the Canva application to create reading books and encyclopedias guided by the presenters. The results of this study are expected to provide teachers with new knowledge about creating reading books and encyclopedias through digital media so that they can increase students' interest in reading. keywords: literacy, workshop, reading books, encyclopedias